Inflation volatility across advanced and emerging economies during the COVID-19 pandemic - Lenin Arango-Castillo; María José Orraca; Regina Brise\~no (Banco de México, 2025)
Using a sample of advanced and emerging economies, this paper studies the volatility of three inflation measures from January 2001 to March 2023, employing variants of the GARCH model that account for the sign, magnitude, and persistence of shocks. The results show that the inflation surge during the COVID-19 pandemic coincided with increased volatility in several countries. However, this is not the norm in the studied period. Descriptive evidence indicates that a strong positive correlation between inflation and its volatility within countries was observed at the beginning of the Global Financial Crisis and during the pandemic, two periods characterized by global inflationary pressures and high commodity prices, whereas in other periods, this correlation is nonexistent or weak.
Keywords: E31; C32; C51; 330; Inflation; Volatility; COVID-19 Pandemic; Global Inflation